The paradigm shift in Danish development policy - Kjær, Anne Mette (Politica, 2020)
How has Danish development policy evolved, and what are the underlying driving forces of these changes? Drawing on Peter Hall’s framework, this article identifies recent changes in Danish development policy as a gradual shift of policy paradigm during the years in the new millennium. The size of development aid, the use of policy instruments, and the goal hierarchies in development policy all changed. The proportion of aid to GNI has been reduced by more than 30 percent, the composition of aid has changed in that allocations for country programs in the poorest countries have declined. Finally, the overall purpose of aid is no longer solely poverty reduction. In explaining these changes, the article shows that they emerged as a result of a politicization of aid preceded by a shift in the locus of authority.